Pemenuhan Asas Peradilan Sederhana, Cepat dan Biaya Ringan Dalam Penyelesaian Perkara Melalui Aplikasi E-Court dan E-Litigasi - Reza Dwi Ardianto; Taufiqurrahman Syahuri; Mardi Chandra (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Judicial principles related to the fulfillment of the principle of quick, simple and low costs in the practice of trial in the Court have so far been considered difficult to fulfill. This is due to the technical administrative and technical judicial rigid procedural demands which are executed precisely in order to achieve the legal requirements and fit. This then triggered the Supreme Court to make a breakthrough in judicial reform by launching e-court and e-litigation. However, through PERMA which oversees e-court and e-litigation, it is worth analyzing whether it is able to fulfill the principles of justice related to the fulfillment of the principles of fast, simple and low cost. The research problems consist of: How is the use of e-court and e-litigation applications in achieving the fulfillment of simple, fast, and low-cost judicial principles? and How is the application of the content of the norms of e-court and e-litigation in court practice, especially related to electronic procedural law?Keyword: AbstrakAsas peradilan terkait pemenuhan asas cepat, sederhana, biaya ringan dalam praktik persidangan di Pengadilan selama ini dianggap sukar terpenuhi. Hal ini diakibatkan oleh teknis administrasi dan teknis yustisial yang rigid dan procedural dimana menuntut dilaksanakan secara tepat agar tercapai syarat sah dan patut.  Hal ini kemudian memicu Mahkamah Agung untuk melakukan terobosan pembaharuan peradilan dengan melaunching e-court dan e-litigasi. Namun demikian melalui PERMA yang menaungi e-court dan e-litigasi patut dianalisis apakah mampu memenuhi Asas peradilan terkait pemenuhan asas cepat, sederhana, biaya ringan. Permasalahan penelitian terdiri dari: Bagaimana pemanfaatan aplikasi e-court dan e-litigasi dalam mencapai pemenuhan asas peradilan sederhana, cepat, dan biaya ringan? dan Bagaimana penerapan muatan norma e-court dan e-litigasi dalam praktik persidangan utamanya terkait dengan hukum acara secara elektronik?Kata Kunci: Peradilan Sederhana; E-court; E-litigasi